Base dez: o grande tesouro matemático e sua aparente simplicidade - Rodrigues, Wanda S (2001)
The present study has as a central task to identify the way on the construction of the numerical writing and its usage through the fundamental teaching. The objective is to contribute for the elaboration of more consistent didactic proposals, which may consider students previous knowledge and possible obstacles during the process. Part of the historical analysis on the construction of numeration systems and the numerical writing in different civilizations has evidenced the decimal basis as a great mathematical treasure. It also brings up the history of the numeral system that has been taught on the first years of the fundamental school for the last few decades. The investigation is based on studies of numerical writing constructions and showed, for example, that the process and procedures involved in the grouping and exchanges on the ten basis takes much more time to be built than it was previously thought. Based on the children answers and on the different steps of the fundamental teaching, the study presents an analysis of the relationship between the school knowledge and that socially constructed by the students. It shows that the evolution of these knowledge is not linear and emphasizes the need of a consistent work related to the numerical writing productions to the mental and written calculation and for the resolution of problems that involve natural and rational numbers presented in decimal form